2017
DOI: 10.1002/chem.201700844
|View full text |Cite
|
Sign up to set email alerts
|

Insights into trans‐Ligand and Spin‐Orbit Effects on Electronic Structure and Ligand NMR Shifts in Transition‐Metal Complexes

Abstract: Surprisingly general effects of trans ligands L on the ligand NMR shifts in third-row transition-metal complexes have been found by quasi-relativistic computations, encompassing 5d , 5d , and to some extent even 5d situations. Closer analysis, with emphasis on H shieldings in a series of linear HAu L complexes, reveals a dominance of spin-orbit (SO) effects, which can change sign from appreciably shielding for weak trans ligands to appreciably deshielding for ligands with strong trans influence. This may be tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
74
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(83 citation statements)
references
References 61 publications
9
74
0
Order By: Relevance
“…10 We note in passing that this finding is consistent with previous theoretical studies on HALA (heavy-atom-effects on the lightatom) "spin-orbit" shifts in transition-metal and actinide complexes. 34,36,[50][51][52][53][54][55][56] Similarly, owing to the large hydrogen 1s-orbital contribution to the An-H bonding, as-yet elusive uranium(VI)…”
Section: H Nmr Spectra Of Crude Mixturesmentioning
confidence: 99%
“…10 We note in passing that this finding is consistent with previous theoretical studies on HALA (heavy-atom-effects on the lightatom) "spin-orbit" shifts in transition-metal and actinide complexes. 34,36,[50][51][52][53][54][55][56] Similarly, owing to the large hydrogen 1s-orbital contribution to the An-H bonding, as-yet elusive uranium(VI)…”
Section: H Nmr Spectra Of Crude Mixturesmentioning
confidence: 99%
“…Kaupp and co‐workers showed that the trans ligand influence is related with the Au‐H bond lengths in HAuL complexes and the observed correlations between hydride shifts and Au‐H distances arise indirectly from the effect of the trans ligand on the polarization of the metal d (and p ) orbitals, which in turn affects both the structures and the hydride shifts. Accurate linear correlations between σ SO ( 15 N) and the Au−N distances in a series of Au(I) complexes were also reported .…”
Section: Resultsmentioning
confidence: 81%
“…Magnetic shielding tensors have been computed with the gauge‐including atomic orbitals DFT method, as implemented in the Gaussian09 series of programs. It is well established that relativistic and spin orbit effects besides influencing the NMR signal of the heavy atom (HA) itself (HAHA effect), the NMR chemical shifts of the light atoms (LA) bound to the HA center are affected as well (HALA effect) and therefore strongly contribute to computed isotropic magnetic shielding constants in Pt(II) coordination compounds . In this context, 35 Cl shielding constants were calculated by inclusion of scalar relativistic effects and switching on the DKH approximation as implemented in the Gaussian 09 program suite.…”
Section: Computational Detailsmentioning
confidence: 99%
See 2 more Smart Citations